Resilience in times of disruptions: Perspectives from Thai pre-service English teachers - Jariya Sairattanain; Thiwaporn Thawarom; Daron Benjamin Loo (Association of Southeast Asian Teacher Education Network (AsTEN), 2025)
Amidst disruptions in the education, resilience has emerged as a vital quality for educators. This study aimed to explore the nature of resilience as a dynamic construct from the perspectives of Thai pre-service English teachers (n=115), who were recruited through convenience sampling. Using thematic analysis of qualitative data, four key themes were identified: maintaining a positive outlook and sense of control, developing flexibility, being in a supportive environment and inspiring growth in others. These findings highlight the multifaceted nature of resilience and how personal attributes, professional support, and institutional conditions shape it. This renders resilience as a dynamic and context-dependent construct rather than one that is fixed. Teacher education programs, especially in the ASEAN context, should recognize resilience as an important construct to be familiarized among pre-service teachers. This would ensure that these future teachers would be prepared to address challenges or opportunities that arise in their work environment.